2017
DOI: 10.5301/jva.5000742
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Three Types of Native Arteriovenous Fistula in a Single Center

Abstract: D-AVF is still the gold-standard access for hemodialysis. If D-AVF is not possible, MA-AVF should be always investigated before committing to a P-AVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…2 One institutional study showed the 1-year functional patency of distal, midarm, and proximal AVF to be 80.5%, 75.8%, and 61.5%, respectively. 3 It is important to create vascular access with as few complications as possible and to develop techniques that prolong the functional patency of AVFs. With many patients waiting for kidney transplantation, an important area of research is the identification and use of techniques that extend the functional patency of each AVF.…”
mentioning
confidence: 99%
“…2 One institutional study showed the 1-year functional patency of distal, midarm, and proximal AVF to be 80.5%, 75.8%, and 61.5%, respectively. 3 It is important to create vascular access with as few complications as possible and to develop techniques that prolong the functional patency of AVFs. With many patients waiting for kidney transplantation, an important area of research is the identification and use of techniques that extend the functional patency of each AVF.…”
mentioning
confidence: 99%
“…1,7 Varios estudios han demostrado que la FAV distal clásica tiene una mayor tasa de fracaso temprano (trombosis temprana o maduración fallida) sin embargo, se realiza como primera opción cuando la vena y la arteria son adecuadas, pero es factible en solo el 13% de los pacientes. 8 El AAV ulnar basílico (FAV-UB) podría ser una alternativa con tasas de permeabilidad primaria y secundaria aceptables, cuando no es posible FAV-RC debido a la mala calidad de las venas. 7 El injerto AV (IAV) se crea cuando el paciente no tiene venas adecuadas o FAV fallida.…”
Section: Discussionunclassified
“…Distal radiyosefalik fistüller yüksek açıklık ve düşük komplikasyon oranıyla önerilen altın standart damar erişim yoludur ve tüm hastalar mutlaka distal bölgeden fistül girişimine uygunluk açısından değerlendirilmelidir. [16,17] Proksimal radiyosefalik fistül girişimi teknik olarak daha zordur, bu bölgede radiyal arter daha derinde bulunur, özellikle obez hastalarda bu girişim daha yorucu ve zaman alıcıdır. Bu fistülde de inflow olarak radiyal arter kullanıldığı için fistüle bağlı distal iskemi oluşma riski daha düşüktür.…”
Section: Discussionunclassified